{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

COT3100Hmk04Sol

# COT3100Hmk04Sol - COT 3100 Fall 2002 Homework#4 Solutions 1...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: COT 3100 Fall 2002 Homework #4 Solutions 1) Use induction on n ≥ 1 to prove the following summation formula: . 9 ) 2 )( 1 3 ( 2 ) 2 ( 1 + =- + +- =- ∑ n n i i n i Base case: n=1 LHS = 2 ) 2 ( 1 0(-2) ) 2 ( 1 1- =- + =- ∑ = i i i RHS = 2 9 18 9 4(4) 2 9 ) 2 )( 1 ) 1 ( 3 ( 2 1 1- =- = +- =- + +- + Thus, the formula is true for n=1. Inductive hypothesis: Assume for an arbitrary n=k that . 9 ) 2 )( 1 3 ( 2 ) 2 ( 1 + =- + +- =- ∑ k k i i k i Inductive Step: Under that assumption prove for n=k+1 that 9 ) 2 )( 4 3 ( 2 9 ) 2 )( 1 ) 1 ( 3 ( 2 ) 2 ( 2 1 ) 1 ( 1 + + + + =- + +- =- + + +- =- ∑ k k k i i k k i 1 1 ) 2 )( 1 ( ) 2 ( ) 2 ( + = + =- + +- =- ∑ ∑ k k i i k i i k i i 1 1 ) 2 )( 1 ( 9 ) 2 )( 1 3 ( 2 + +- + +- + +- = k k k k 9 ) 2 )( 1 ( 9 9 ) 2 )( 1 3 ( 9 2 1 1 + +- + +- +-- = k k k k 9 )) 1 ( 9 ( ) 1 3 (( ) 2 ( 9 2 1 +- +--- = + k k k 9 ) 9 9 1 3 ( ) 2 ( 9 2 1-- +--- = + k k k 9 ) 8 6 ( ) 2 ( 9 2 1----- = + k k 9 ) 4 3 )( 2 ( ) 2 ( 9 2 1 +---- = + k k 9 ) 4 3 ( ) 2 ( 9 2 2 +...
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

COT3100Hmk04Sol - COT 3100 Fall 2002 Homework#4 Solutions 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online